Comprehensive Investigation of General Medicine, Nursing and Laboratory Medicine for an Integrate Care Opportunity (The Review of Diabetic Studies, 2025)
The modern health care functions as an entity with the combined effect of three fundamental components: general medicine, nursing, laboratory medicine. The present comprehensive review will address their interrelatedness and cooperative relationships as well as the synergistic influence of technological advances on patient care. This study covers about 6000 words and analyzes the pedagogical contexts, professional roles, technological developments and ethical considerations that shape both domains. This research indicates that it is not sufficient in health-care to have excellent individual disciplines without the coordinated activity of multidisciplinary teams. This study sheds light on how these three pillars are evolving to address shifts in population health, advances in technology, and transformations of the healthcare system based on current experience, emerging trends, and challenges for the future. The results highlight the fact that it is critical to continue investment in interprofessional education, EBP integration and quality improvement programs to maintain equitable care delivery.